Acute toxicity of chemically and mechanically dispersed crude oil to juvenile sea bass (Dicentrarchus labrax): Absence of synergistic effects between oil and dispersants. (7th May 2015) - Dussauze, Matthieu; Pichavant‐Rafini, Karine; Le Floch, Stéphane; Lemaire, Philippe; Theron, Michaël
Abstract The goal of the present experiment was to assess the relative acute toxicities of mechanically and chemically dispersed oil (crude Arabian Light) in controlled conditions. Juvenile sea bass (Dicentrarchus labrax) were exposed to 4 commercial formulations of dispersants (Corexit EC9500A, Dasic Slickgone NS, Finasol OSR 52, Inipol IP 90), to mechanically dispersed oil, and to the corresponding chemical dispersions. Acute toxicity was evaluated at 24 h, 48 h, 72 h, and 96 h through the determination of 10%, 50%, and 90% lethal concentrations calculated from measured total petroleum hydrocarbon (TPH) concentrations; Kaplan–Meyer mortality analyses were based on nominal concentrations. Animals were exposed to the dissolved fraction of the oil and to the oil droplets (ranging from 14.0 μm to 42.3 μm for the chemical dispersions). Kaplan–Meyer analyses demonstrated an increased mortality in the case of chemical dispersions. This difference can be attributed mainly to differences in TPH, because the chemical lethal concentrations were not reduced compared with mechanical lethal concentrations (except after 24 h of exposure). The ratios of lethal concentrations of mechanical dispersions to the different chemical dispersions were calculated to allow direct comparisons of the relative toxicities of the dispersions. The results ranged from 0.27 to 3.59, with a mean ratio close to 1 (0.92). These results demonstrate an absence of synergistic effect between oil and chemical dispersants in an operational context. Environ Toxicol Chem 2015;34:1543–1551. © 2015 SETAC